Aplikasi Komposit pada Permukaan Cetakan: Eksplorasi Teknik Kerajinan pada Medium Komposit Sabut Kelapa - Wiguna, Iqbal Prabawa; Hernawan, Abbyzar Raffi (JURNAL RUPA, 2022)
This article explores the creation of craft techniques through the process using coconut fiber composites as a medium for arts and crafts. The study highlights the outer casting composite technique, coconut fiber processing techniques using hand skills which are the result of practical exploration by the author’s to create three-dimensional objects made from coconut fiber composites, hopefully this technique can be applied and developed further as an innovation for arts and crafts techniques using the cocopeat as medium. This technique combines the putty technique which is generally used in wood medium with the basic paper fingers pressing technique in papier mache, and then the technique applied to the coconut fiber composite. The research uses qualitative methods and practice led research, the author’s completed the research with the documents and data on creative activity processes such as exploration of the medium, techniques, theories and contextualization. The outer casting composite technique will cover several stages, starting from material preparation, making the composite dough, sticking the dough to the casting, putty and sanding, and finally coating or finishing the composite materials. The outcome of this research is the innovation of craft techniques using coconut fiber composite material which is applied for the making of a lampshade with the presenting data in the form of a documentation process.